A review of the possibilities of utilising medicinal plants in improving the reproductive performance of male ruminants. Issue 1 (31st December 2022) - Shai, K.; Lebelo, S. L.; Ng'ambi, J. W.; Mabelebele, M.; Sebola, N. A.
ABSTRACT: Our review condensed evidence on the potential of medicinal plants to improve the reproductive performance of livestock. The success of any livestock farming operation is highly dependent on the reproductive performance of animals. However, infertility has limited the proficiency of livestock and resulted in economic losses. For centuries, farmers utilised medicinal plants extensively in managing reproductive disorders. These plants have few to no side effects, are cheap, easily accessible and readily available. Among others, the inclusion of Moringa olifera leaf extracts for 14 days at levels of 100–300 mg/kg body weight improved sperm characteristics. Zingiber officinale root extracts at levels of 500–1000 mg/kg body weight for 3 weeks increased sperm count, viability and mobility and testosterone. Furthermore, the increase in the volume of ejaculate and sperm concentration has been observed in sheep when Leucaena spp were added to their diets at 100–300 g/sheep/day for 60 days. However, there is little literature regarding the use of medicinal plants on ruminants, as the majority of studies have been laboratory-based and have used experimental animals, including rats and mice. Thus, future research is required through in vivo and in vitro studies to ascertain the efficacy of these medicinal plants in male ruminants.